Case report on adenoid cystic carcinoma of palate with review of literature (Indian Journal of Case Reports, 2022)
Adenoid cystic carcinoma (ACC) is a malignant tumor of minor salivary glands of the oral cavity, particularly the palate which accounts for about 5–10%. These tumors are slow growing with a high incidence of local recurrence, perineural invasion, and distant metastasis. Here, we report the case of a 69-year-old female who presented with swelling over the hard palate. Computerized tomography shows enhancing lesion along the undersurface of the left side of the hard palate, abutting the maxillary alveolus in the region of the second premolar and first two molars. There was no erosion of the inner cortex of the maxillary alveolus and no extension into the nasal cavity. Following the biopsy, she underwent a left hard palatectomy with upper alveolar resection. The final histopathological report confirmed ACC with no perineural invasion. Following she received adjuvant radiotherapy using an intensity-modulated radiotherapy technique. Now at 6 months of follow-up, there was no evidence of recurrence. Thus, our patient requires long-term follow-up to assess the benefit and survival outcome.